2013
DOI: 10.1175/jamc-d-12-0224.1
|View full text |Cite
|
Sign up to set email alerts
|

Likely Ranges of Climate Change in Bolivia

Abstract: Bolivia is facing numerous climate-related threats, ranging from water scarcity due to rapidly retreating glaciers in the Andes to a partial loss of the Amazon forest in the lowlands. To assess what changes in climate may be expected in the future, 35 global circulation models (GCMs) from the third and fifth phases of the Coupled Model Intercomparison Project (CMIP3/5) were analyzed for the Bolivian case. GCMs were validated against observed surface air temperature, precipitation, and incoming shortwave (SW) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…Farmers' perceptions of climate change in the eight study communities are in line with empirical data and other studies on farmers' perceptions in the Andean highlands (Perez et al 2010;Thibeault et al 2010;Valdivia et al 2010;McDowell and Hess 2012;Seiler et al 2013;Lennox 2015). The increasing problem of pests and diseases experienced by farmers is associated with rising temperatures and further exacerbated by shifts towards monoculture, pest-susceptible varieties, and abbreviated crop rotation schedules (Parsa 2010;Perez et al 2010;McDowell and Hess 2012;Poveda et al 2012).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Farmers' perceptions of climate change in the eight study communities are in line with empirical data and other studies on farmers' perceptions in the Andean highlands (Perez et al 2010;Thibeault et al 2010;Valdivia et al 2010;McDowell and Hess 2012;Seiler et al 2013;Lennox 2015). The increasing problem of pests and diseases experienced by farmers is associated with rising temperatures and further exacerbated by shifts towards monoculture, pest-susceptible varieties, and abbreviated crop rotation schedules (Parsa 2010;Perez et al 2010;McDowell and Hess 2012;Poveda et al 2012).…”
Section: Discussionsupporting
confidence: 75%
“…High interannual variability in precipitation is a constant feature of this high altitude plateau, due to periodic climate oscillations (e.g. El Niño) that bring drought in some years and floods in others (Seiler et al 2013). Indigenous farmers have traditionally managed this unpredictable and harsh environment by using drought-and frosttolerant crops, keeping many crop varieties, and planting across multiple plots to disperse risk and take advantage of high spatial heterogeneity, among other strategies (Halloy et al 2005;Perez et al 2010;McDowell and Hess 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their results, frost days are projected to decrease by 2-4 standard deviations in all scenarios by the end of the 21st century when compared to the reference year 2000, while warm nights and heat waves will become more frequent by 3-7 standard deviations (warm nights) and 1-4 standard deviations (heat waves) respectively, by the year 2100. More recently Seiler et al (2013b) analyzed both CMIP3 and CMIP5 models over Bolivia to estimate future temperature changes under a range of emission scenarios. According to their results, temperature in Bolivia will increase anywhere from 2.5°C to 6°C by the end of the century compared to the 1961-90 period, depending on model and emission scenario considered.…”
Section: Climate Projectionsmentioning
confidence: 99%
“…The 2010 wildfires resulted in a national state of emergency, which has intensified public debate around wildfires, looking for tangible solutions to prevent potential impacts, particularly given the possibility of more frequent droughts in the future (Ibarnegaray et al 2014). According to regional and global climate model projections, seasonality may become more extreme in the region, with less precipitation during the drier months from July to November (Seiler 2009, Seiler et al 2013. Since the 1990s, Marengo et al (2011) also identified a tendency for a prolonged dry season in southern Amazonia, with a late onset in the wet season.…”
Section: Introductionmentioning
confidence: 99%